Dual-Target Electrochemical Sensor Based on 3D MoS2-rGO and Aptamer Functionalized Probes for Simultaneous Detection of Mycotoxins - Yu, Yanyang; Han, Jie; Yin, Jiaqi; Huang, Jingcheng; Liu, Jing; Geng, Lingjun; Sun, Xia; Zhao, Wenping (Frontiers in Chemistry, 2022)
A dual-target aptamer functionalized probes (DTAFP) was applied for the detection of aflatoxin B1 (AFB1) and zearalenone (ZEN) simultaneously, which has not been reported. Meanwhile, two functional materials for signal amplification of the DTAFP were synthesized: 1) a three-dimensional molybdenum disulfide-reduced graphene oxide (MoS2-rGO) as a favorable loading interface; 2) a double-probes gold nanoparticles (AuNPs) modified by Thionin (Thi) and 6-(Ferrocenyl) hexanethiol (FC6S) as distinguishable and non-interfering signals. Mycotoxins on the electrode surface release into solution under the function of the DTAFP, leading a reduction of the differential peak impulse in signal response. Under the optimum conditions, the aptasensor exhibited a detection range of 1.0 pg mL−1–100 ng mL−1 for AFB1 and ZEN, with no observable cross reactivity. In addition, the aptasensor performed excellent stability, reproducibility, specificity, and favorable recovery in the detection of edible oil. This work demonstrated a novel method for the construction of a simple, rapid, and sensitive aptasensor in the detection of multiple mycotoxins simultaneously.